Deep Learning for Natural Language Processing: Theory and Practice (Tutorial) - He, Xiaodong; Gao, Jianfeng; Deng, Li (CIKM, 2014)
Deep Learning for Natural Language Processing: Theory and Practice (Tutorial) Slideshow